2019
DOI: 10.1186/s12891-019-2990-5
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with osteonecrosis of femoral head after internal fixation of femoral neck fracture:a systematic review and meta-analysis

Abstract: BackgroundAlthough the risk factors associated with osteonecrosis of femoral head (ONFH) after internal fixation of femoral neck fracture (IFFNF) have been frequently reported, the results remain controversial. Therefore, its related risk factors were systematically evaluated and meta-classified in this study.MethodsLiterature on risk factors of ONFH caused by IFFNF was retrieved in PubMed, Embase and Cochrane Library due June 2019. Review Manager 5.3 software was applied to data synthesis, and Stata 13.0 soft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
30
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(35 citation statements)
references
References 31 publications
3
30
0
1
Order By: Relevance
“…An unhealed fracture is subsequently prone to further fixation failure as well as FNS. In addition, fracture displacement is predictive for the occurrence of AVN, which is consistent with previous findings [12][13][14][15] . A digital-subtraction angiographic study showed that vessel damage rates in Garden III and IV types could reach as high as 72.7% −100% [2] .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…An unhealed fracture is subsequently prone to further fixation failure as well as FNS. In addition, fracture displacement is predictive for the occurrence of AVN, which is consistent with previous findings [12][13][14][15] . A digital-subtraction angiographic study showed that vessel damage rates in Garden III and IV types could reach as high as 72.7% −100% [2] .…”
Section: Discussionsupporting
confidence: 92%
“…Demographic characteristics, including age and sex, were collected from patients' medical records. Preoperative medical condition including ISS (Injury Severity Score), general comorbidities, combined fractures, and fracture severity including initial displacement (evaluated by Garden classification) [12][13][14][15] , Pauwels angle [3] , and reduction quality [ 13 , 16 ], was evaluated and determined by two independent surgeons using standard methods; a senior surgeon verified these determinations. These parameters were compared as baseline information to explore the possible selection bias between two fixation groups, and incorporated as confounding parameters in the analysis.…”
Section: Study Design and Patientsmentioning
confidence: 99%
“…It is estimated that the incidence of hip fractures worldwide increases to 2.6 million in 2025 (1). Femoral neck fracture is one of the most common clinical fractures, accounting for 50% of hip fractures (2). The occurrence of femoral neck fracture in young adults is usually caused by high-energy injuries such as traffic injury, fall injury and so on (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Inclusion of some factors was controversial and not considered in our study. For example, in recent years, several studies have suggested retaining internal fixation as a way to reduce the incidence of refracture and necrosis (54). In clinical practice, we also recommend patients to avoid removal of internal fixation, which results in a minimal amount of removal surgeries.…”
mentioning
confidence: 99%
“…A prospective multicenter study is currently underway. Third, some controversial variables were not included in the study because they are either practically uncontrollable or have been proven to be invalid, such as removal of internal fixation, differences in surgery technique, and variability in brands and location of the internal fixation (13,54). A recent study found that variability in location of constructs for the fixation following standard procedures did not significantly affect the outcome (59).…”
mentioning
confidence: 99%